Eculizumab hepatotoxicity in pediatric aHUS - Hayes, Wesley; Tschumi, Sibylle; Ling, Simon C.; Feber, Janusz; Kirschfink, Michael; Licht, Christoph (Pediatric nephrology, 2015)
Eculizumab is a humanized anti-C5 antibody approved for the treatment of atypical hemolytic uremic syndrome (aHUS). Its use is increasing in children following reports of its safety and efficacy.